A field study of the problems of queues at some checkpoints in the city of Baghdad - ابراهيم سماهر طارق (Journal of Economics and Administrative Sciences, 2013)
Abstract Due to the momentum of winning in the streets of the city of Baghdad as a result of the large number of checkpoints so felt researcher to conduct a field visit to find out the main reasons that led to this congestion and to find practical solutions to mitigate wastage winning the arrival time citizen to where you want the least possible time. This research aims to overcome the difficulties experienced by citizens to reach their places of work and reduce waste at the time of service and waiting time as well as reduce the cost of waiting. Has emerged study a set of conclusions, including the use of model queue (G / G / C) and the momentum in the checkpoints Baghdad due to the increase in the number of vehicles in Baghdad and the use of two lines to enter the car, causing confusion where and poor device used in checkpoints and multiplied Adeddalaskhas present in checkpoints note that the only one who uses the device in the control and concern for people, checkpoints to speak with each other and disabled citizens and the presence of four lines at some checkpoints while the user lines which only inefficient persons in the use of the devices in checkpoints and enter the security forces of the same checkpoints allocated to citizens and bring about confusion in the workflow